Local television and the construction of local identities: case studies on two local televisions in Pekanbaru, Indonesia - Dhea Helyana Putri; Puji Rianto; Herman Felani (Asian Journal of Media and Communication, 2018)
This aim of the study is to describe the role of local televisions in constructing local identities. This study was conducted with qualitative approach, examining two programs in two local televisions in Pekanbaru, Riau, Indonesia, namely Belacan Program of Riau Television (RTV) and Online Channel Program of Riau Channel Television (RCTV). This research found that local televisions have important roles in constructing local identities and maintaining local cultures. RTV and RCTV have optimized various ways of constructing local cultures, which simultaneously draws closer relations to their audiences, such as focusing on the Malay culture as a dominant culture in Riau, exploring tourist attractions and new places sursounding the city, delivering the program with local language, presenting traditional clothes worn by the host, involving local comminities in the production and creative processes of the program, innovating the program with the interactive music segment, discussing folk songs, and inviting local speakers. These programs have shown the resistance to the dominance of ‘Jakarta’ and global culture. The use of local language acts as symbolic signs, namely representing the local identities.Keywords: local television; local identity; local culture; creative processes.